Preparation method and application of lithium-sulfur battery diaphragm modified material
By modifying the DHAQ-COF@CNT composite material on the lithium-sulfur battery separator, the problem of polysulfide shuttle effect is solved, and the efficient cycle stability of lithium-sulfur battery and the full utilization of active substances are achieved.
Patent Information
- Application Number
- CN202510588167.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-08
- Publication Date
- 2025-08-01
AI Technical Summary
Existing lithium-sulfur batteries have problems of irreversible losses caused by polysulfide shuttle effect and low utilization rate of active substances.
The separator was modified by DHAQ-COF@CNT composite material, and the shuttle of polysulfides was inhibited through physical adsorption and chemical catalytic conversion. The composite material prepared by reacting the porous structure of carbon nanotubes and Schiff base was used as the lithium-sulfur battery separator modification layer.
Effectively inhibit the shuttle effect of polysulfides, improve the electrochemical performance and utilization of active substances of lithium-sulfur batteries, and improve the cycle stability and rate performance of the battery.
Smart Images

Figure CN120413983A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium-sulfur batteries, and particularly to a preparation method and application of a modified material for a lithium-sulfur battery separator. Background Art
[0002] With the continuous expansion of global economic activities, the dependence of human society on energy supply has shown a significant growth trend. The large-scale development and utilization of traditional fossil energy not only cause severe environmental problems including air pollution and greenhouse effect, but also lead to the risk of exhaustion of non-renewable resources. These dual crises pose a substantial challenge to global sustainable development. The most important is that the over-exploitation of current non-renewable fossil fuel resources has triggered dual crises: on the one hand, the long-term dependence on traditional energy has led to a rapid decline in geological reserves; on the other hand, the continuous release of carbon dioxide (CO2) during the combustion process forms the greenhouse effect, significantly intensifying the trend of global warming. This unsustainable energy utilization pattern has prompted the international community to shift the research focus to a new type of renewable clean energy system, which has become a direction urgently needed to be broken through in the field of energy science and technology. In recent years, the rapid development of various renewable energies (such as solar energy, geothermal energy, wind energy, etc.) has urgently required the development of new and efficient energy storage systems. However, new energy sources such as solar energy and wind energy have problems such as low energy conversion efficiency and unstable energy acquisition. Therefore, it is of great research significance to store and convert new renewable energies through effective methods.
[0003] Among different energy storage systems, lithium-sulfur batteries have received extensive attention. A lithium-sulfur battery is a battery with metallic lithium as the negative electrode and elemental sulfur as the positive electrode, and its theoretical specific energy density is as high as 2600 Wh / kg -1 and its volumetric energy density can reach 2800 Wh / L. -1 In addition, the abundant reserves of sulfur in nature and its non-toxic nature endow the lithium-sulfur battery system with prominent advantages in energy utilization economy and environmental compatibility.
[0004] In view of the defects and limitations of lithium-sulfur batteries, it is necessary to study new methods to prepare new products that can enhance the catalytic conversion of polysulfides and avoid irreversible loss of active substances. Summary of the Invention
[0005] (I). Technical Problems to be Solved
[0006] Aiming at the problems and deficiencies existing in the prior art, the purpose of the present invention is to provide a preparation method and application of a modified material for a lithium-sulfur battery separator.
[0007] (II). Technical Solutions
[0008] To solve the above technical problems, the technical solution provided by the present invention is as follows: A preparation method of a modified material for a lithium-sulfur battery separator, comprising the following steps:
[0009] Step 1: Weigh 113.5 mg of 1,5-diamino-4,8-dihydroxyanthraquinone (DADHAQ), 60 mg of 2,4,6-triformylphloroglucinol (TP), and 30 mg of carbon nanotubes (CNT), and prepare the DHAQ-COF@CNT composite material through a Schiff base reaction. After the reaction is completed, wash and dry to obtain the composite material;
[0010] Step 2: Disperse the composite material and polyvinylidene fluoride (PVDF) in N-methylpyrrolidone (NMP) in a certain proportion to obtain a dispersion solution, and then perform vacuum filtration to uniformly deposit the composite material on the surface of the PP separator;
[0011] Step 3: Perform vacuum drying on the modified separator to obtain a modified separator for a lithium-sulfur battery.
[0012] As an improvement: The carbon nanotubes (CNT) are amino-functionalized carbon nanotubes, and the mass ratio thereof is 30%.
[0013] As an improvement: The temperature of the Schiff base reaction is 120 °C, and the reaction time is 72 hours.
[0014] As an improvement: The ratio of DHAQ-COF@CNT to PVDF in the preparation of the modified separator for a lithium-sulfur battery by vacuum filtration is 9:1.
[0015] As an improvement: The vacuum drying temperature of the modified separator is 60 °C, and the time is 12 hours.
[0016] An application of a modified separator for a lithium-sulfur battery, in which a lithium-sulfur battery is made by subjecting the modified separator prepared by the method as claimed in claim 1, a positive electrode sheet, and an electrolyte to processes of pair rolling, sheet making, assembly, liquid injection, and sealing.
[0017] (III) The present invention has the following advantages: After the separator is modified with the DHAQ-COF@CNT composite material, it has an adsorption effect on polysulfides, can inhibit the shuttle effect of the battery, and the material, as a modified layer, inhibits the polysulfide shuttle through physical adsorption and chemical catalytic conversion.
[0018] First, the porous structure of DHAQ-COF@CNT itself provides a large number of adsorption sites to intercept LiPSs and provides an effective physical adsorption effect. In addition to physical adsorption, more importantly, chemical adsorption and catalytic conversion. The C=O in DHAQ-COF@CNT has reversible redox activity, and during the charge and discharge process, these carbonyl groups can participate in the catalytic conversion of polysulfides through the acceptance and release of electrons;
[0019] Secondly, the amino and hydroxyl groups in the structure can immobilize LiPS through Lewis acid-base interaction. The lone pair electrons of the amino group can form coordination bonds with the sulfur atoms of polysulfides, inhibiting their dissolution and shuttle effect. The hydroxyl group enhances the adsorption ability of LiPS through hydrogen bonding;
[0020] Thirdly, the β-ketoenamine bond, as the connecting bond of the COF framework, can also generate additional active sites.
[0021] In summary, the DHAQ-COF@CNT composite as a lithium-sulfur battery separator modification material can provide more effective chemical adsorption and catalytic conversion, effectively improving the electrochemical performance of lithium-sulfur batteries. Description of the Drawings
[0022] Figure 1 is a schematic diagram of the vacuum filtration method;
[0023] Figure 2 is a schematic diagram of the contact angle between the modified separator and the electrolyte;
[0024] Figure 3 is a graph of the 1000-cycle performance of a lithium-sulfur battery at 1.0C;
[0025] Figure 4 is a graph of the rate performance of a lithium-sulfur battery at different rates;
[0026] Figure 5 is a cyclic voltammogram of a lithium-sulfur battery at different sweep rates. Detailed Embodiments
[0027] In order to make the objectives, technical solutions, and beneficial technical effects of the present invention clearer and more understandable, the present invention will be further described in detail below with reference to the drawings and specific embodiments. It should be understood that the specific embodiments described in this specification are only for explaining the present invention and not for limiting the present invention.
[0028] Example 1
[0029] A preparation method of a lithium-sulfur battery separator modification material is as Figure 1 shown in the production method of the modified separator. DHAQ-COF@CNT and polyvinylidene fluoride (PVDF) are dispersed in 5 mL of N-methylpyrrolidone (NMP) solvent according to a mass ratio of 9:1 (27 mg: 3 mg), and ultrasonic treatment is performed for 5 minutes to form a homogeneous dispersion. The dispersion is subjected to vacuum filtration, and DHAQ-COF@CNT is deposited on the surface of the PP separator. It is dried in a vacuum oven at 60 °C for 12 hours, and the dried modified separator is cut into circular pieces with a diameter of 19 mm. The areal density of DHAQ-COF@CNT is about 0.6 mg cm -2 .
[0030] Example 2
[0031] A preparation method of a lithium-sulfur battery separator modification material. Weigh 49 mg of sulfur electrode material, 14 mg of Ketjenblack, and 7 mg of polyvinylidene fluoride (PVDF) according to a mass ratio of 7:2:1, add 400 μL of N-methylpyrrolidone (NMP) solvent, and form a uniform active material slurry through sufficient grinding. Subsequently, the mixed slurry is evenly coated on a carbon-coated aluminum foil current collector by the doctor blade method, and placed in a vacuum drying oven, and dried at 60 °C for 12 hours. The dried electrode sheet is cut into circular samples with a diameter of 12 mm for standby. The sulfur areal density of the prepared electrode is about 1.5 mg cm -2 .
[0032] Example 3
[0033] Application of the modified separator of lithium-sulfur battery. All batteries use CR2032 type button battery cases and are assembled in a glove box environment. The sulfur-carbon composite electrode on the carbon-coated aluminum foil and the commercial lithium foil are cut into circular pole pieces with a diameter of 12 mm as the positive electrode, and the commercial PP separator and the prepared composite material intermediate layer are cut into circular pieces with a diameter of 19 mm as the battery separator.
[0034] After the battery assembly is completed, it is left standing for 24 hours and then the electrochemical performance test is carried out.
[0035] Performance test of the lithium-sulfur battery of the present invention
[0036] Figure 2 It is a comparison diagram of the contact angles of the electrolyte with the PP separator and the DHAQ-COF@CNT modified separator at 0 s and 2 s. Figure 2 The contact angle measurement results of the commercial separator and the modified separator are shown. The initial contact angle of the commercial separator is 67.6°, and after standing for 0.2 seconds, its contact angle only drops to 62.5°. This indicates that the commercial separator has poor wettability to the electrolyte. During the operation of the battery, it is difficult for the electrolyte to quickly infiltrate the separator, thus hindering the lithium ion transport. In contrast, the DHAQ-COF@CNT modification layer shows an instantaneous absorption characteristic when contacting with the electrolyte. This is because there are hydroxyl groups and other polar groups on the main chain of the DHAQ-COF@CNT molecule, making it show good electrolyte affinity. In addition, the contact angle between the DHAQ-COF@CNT modified separator and the electrolyte is close to 0°, further indicating that the presence of the DHAQ-COF@CNT modification layer is beneficial to the infiltration of the electrolyte, greatly improving the affinity for the electrolyte and then promoting Li+ transport, and improving the electrochemical performance of the battery.
[0037] On a blue electrochemical test instrument, the inventor detected the cycle performance of the lithium-sulfur battery at 1.0C for 1000 cycles, and the results are as Figure 3As shown. Since the lithium-sulfur battery separator contains a lithium-sulfur battery separator modification material, the rich defect structure of the lithium-sulfur battery separator modification material can better anchor polysulfides, hinder the irreversible loss of polysulfides caused by the passage of polysulfides from the positive electrode through the separator to the negative electrode, so that the lithium-sulfur battery can still maintain a high specific capacity after 1000 long cycles. The lithium-sulfur battery with the DHAQ-COF@CNT modified separator has an initial discharge specific capacity of 1286 mAh g -1 and has a high capacity retention rate. After 1000 charge-discharge cycles, the capacity is as high as 415 mAh g -1 , which is mainly because during the discharge process, the abundant functional groups on the surface of the DHAQ-COF@CNT material provide sufficient adsorption sites for lithium polysulfide, effectively preventing the transmembrane migration of lithium polysulfide. At the same time, the redox active sites on the material surface accelerate the conversion process of liquid lithium polysulfide to solid lithium sulfide, which significantly improves the utilization rate of active substances, thus effectively alleviating the shuttle effect.
[0038] On the Blue Electric test instrument, the inventors detected the rate performance of the lithium-sulfur battery, and the results are as Figure 4 shown. Due to the presence of the separator modification material in the lithium-sulfur battery, its rich defect structure can accelerate the rapid conversion of long-chain polysulfides into lithium sulfide. At the same time, it can ensure the rapid progress of reversible conversion, enabling the lithium-sulfur battery to maintain a fast kinetic conversion rate at different current densities, and further enabling the reversible specific capacity of the lithium-sulfur battery to remain at a high level. The battery assembled with the DHAQ-COF@CNT intermediate layer has discharge specific capacities of 1381, 799, 580, 477, and 354 mAh g -1 at current densities of 0.1, 0.2, 0.5, 1.0, and 2.0 A g -1 , and when the current density returns to 0.1 A g -1 , the specific capacity can still recover to 1070 mAh g -1 , and the capacity retention rate is 77.6%. It shows that the battery assembled with the modified separator can effectively inhibit the shuttle of lithium polysulfide and has excellent performance.
[0039] The inventors used the Shanghai Chenhua CHI660E electrochemical workstation to test the cyclic voltammetry curve of the lithium-sulfur battery at a scanning voltage of 1.7 - 2.8 V and scanning speeds of 0.1, 0.2, 0.3, and 0.4 mV s -1 , and the results are as Figure 5 shown. In the voltage range of 1.8 to 2.7 V, the CV curve of the battery was obtained at a scanning rate of 0.1 mV s -1 . During the discharge process, two characteristic reduction peaks were observed near 2.2 V and 2.0 V, corresponding to the reduction of elemental sulfur to soluble long-chain polysulfide (Li2S n, (4 ≤ n ≤ 8) and the process of further reduction to the final discharge product (Li2S2 / Li2S). During charging, the oxidation peak at 2.5 V corresponds to the reaction of Li2S2 / Li2S being converted to polysulfide and finally oxidized back to elemental sulfur. At the same time, in the battery with the DHAQ-COF@CNT modified separator, a peak located on the charging side can be clearly observed, indicating that the separator modified with the DHAQ-COF@CNT interlayer can oxidize more polysulfides. Figure 5 The phenomenon shown is attributed to the fact that DHAQ-COF@CNT has abundant redox active sites, which can effectively limit and convert polysulfides into sulfur. In addition, the battery with the DHAQ-COF@CNT interlayer exhibits a significantly enhanced peak current intensity and an increased integral area of the CV curve, indicating that the modified separator effectively limits polysulfides, thereby improving the battery capacity.
[0040] It should be noted that in this article, relational terms such as first and second are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any actual relationship or order between these entities or operations. Moreover, the term "comprising", "including" or any other variant thereof is intended to cover non-exclusive inclusion, so that a process, method, article or device comprising a series of elements not only includes those elements, but also includes other elements not expressly listed, or elements inherent to such process, method, article or device.
[0041] Although the embodiments of the present invention have been shown and described, for those of ordinary skill in the art, it can be understood that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the present invention. The scope of the present invention is defined by the appended claims and their equivalents.
[0042] The above describes the present invention and its implementation manners, and this description is not restrictive. Generally speaking, if those of ordinary skill in the art are inspired by it and, without departing from the purpose of the present invention, design similar structural manners and embodiments without creative efforts, they shall fall within the protection scope of the present invention.
Claims
1. A preparation method of a material for modifying a separator of a lithium-sulfur battery, characterized in that, It includes the following steps: Step 1: Weigh 113.5 mg of 1,5-diamino-4,8-dihydroxyanthraquinone (DADHAQ), 60 mg of 2,4,6-triformylphloroglucinol (TP), and 30 mg of carbon nanotubes (CNT). Prepare the DHAQ-COF@CNT material through a Schiff base reaction. After the reaction, wash and dry to obtain the composite material; Step 2: Disperse the composite material and polyvinylidene fluoride (PVDF) in N-methylpyrrolidone (NMP) to obtain a dispersion solution, and then perform vacuum filtration to uniformly deposit the composite material on the surface of the PP separator; Step 3: Vacuum dry the modified separator to obtain the modified separator for lithium-sulfur batteries.
2. The preparation method of a material for modifying a separator of a lithium-sulfur battery according to claim 1, characterized in that: The carbon nanotubes (CNT) are amino-functionalized carbon nanotubes, and the mass ratio it occupies is 30%.
3. The preparation method of a material for modifying a separator of a lithium-sulfur battery according to claim 2, characterized in that: The temperature of the Schiff base reaction is 120 °C, and the reaction time is 72 hours.
4. The preparation method of a material for modifying a separator of a lithium-sulfur battery according to claim 2, wherein: In the preparation of the modified separator for lithium-sulfur batteries by the vacuum filtration method, the ratio of DHAQ-COF@CNT to PVDF is 9:
1.
5. The preparation method of a material for modifying a separator of a lithium-sulfur battery according to claim 4, characterized in that: The temperature for vacuum drying the modified separator is 60 °C, and the time is 12 hours.
6. Application of a modified separator for a lithium-sulfur battery, characterized in that: The modified separator prepared by the preparation method according to claim 1, together with the positive electrode sheet and the electrolyte, is made into a lithium-sulfur battery through processes such as pair rolling, sheet making, assembly, liquid injection, and sealing.